Pelatihan Pembuatan Media Pembelajaran Berbasis Mobile Menggunakan PowerPoint Bagi Guru-guru SMP, SMK dan SMA Di Kabupaten Cilacap - Isa Bahroni; Riyadi Purwanto; Nur Wahyu Rahadi (Politeknik Negeri Cilacap, 2019)
E-learning or electronic learning is a concept of learning carried out through electronic media networks. The development of highly advanced technology in the modern era and globalization enables various activities to be carried out quickly and efficiently. The development of technology has a lot of influence on our way of life, one of which is in the field of education with the use of e-learning. One of the developments in the telecommunications sector that is growing rapidly is cellular phones. Java is the standard language for making Android applications. If you have never studied java, you will have difficulty learning android. PowerPoint applications that are part of Microsoft Office are tools that can be manipulated to design a learning application that is quite attractive. Grafting ispring and saktibuider tools on powerpoint then the process of making an android application does not need to think about coding which is quite boring especially for beginners. The learning model will be made easier if every subject teacher can make learning by summarizing the subject book being taught using the Android-based application model. The application can be accessed by students as handbooks that can be read at any time using an Android smartphone, of course this will facilitate students in learning, especially elementary, middle and high school students